Effect of a common diet and regular beverage on enamel erosion in various temperatures: an in-vitro study. - Zahra Khamverdi; Mohammad Vahedi; Shermin Abdollahzadeh; Mohammad Hosein Ghambari (Tehran University of Medical Sciences, 2013)
This study compared diet and regular Coca-Cola on enamel erosion in cold and room temperatures.Seventy five enamel specimens were prepared and divided into 5 equal groups (N=15) as follows: Group 1: regular beverage at room temperature, Group 2: regular beverage at refri-gerator temperature, Group 3: diet beverage at room and Group 4: diet beverage at refrige-rator temperature. The specimens were immersed in the regular or diet beverage (Coca-Cola, trade mark regd. Khoshgovar Co., Tehran, Iran) at room (20°C) or refrigerator (2°C) temperatures for 20 minutes, 3 times per day for 7 days. Specimens in the control subjects (group 5) were placed in synthetic saliva at room temperature for 7 days. The hardness of specimens was tested using Vickers test under 500 gr loads for 5 seconds. The data were analyzed using two-way ANOVA and Tukey tests.The mean and standard deviations of micro-hardness values of the studied groups were as follow: G1: 304.26±29.71, G2: 285.53±42.14, G3: 279.06±39.52, G4: 266.80±23.98 and G5: 319± 30.79. There was a significant difference in the beverage type as the main factor (p0.05). Tukey tests showed that there were significant differences between control and diet groups as well as regular and diet groups.Diet Coca-Cola is more erosive than the regular type and the temperature of the beverages used had no significant influence on enamel erosion.